Health Services in Hospitals in Utilizing Health Law Expert - Yusriando Yusriando (Wacana Hukum, 2020)
The research objective is to understand and analyze health services in hospitals in utilizing health legal experts. The research paradigm used is the constructive paradigm. Research Specifications, which are used are Analytical descriptive categories. The research approach method used is socio legal research. The types of data needed in this study include primary and secondary data. Data Collection Techniques with Literature Study, Observation, and Interview. Data Analysis in this research is a qualitative descriptive analysis with inductive methods. The results showed that the utilization of health legal experts in health services in hospitals today is very far from the expectations known from the many who still do not understand what health lawyers are and what are the benefits for hospitals. Problems with the lack of use of health legal experts at the hospital at this time are very numerous, such as the socialization of laws and regulations in the health sector that is not running optimally, the number of patient complaints about health services, malpractice cases occur everywhere and feelings of discrimination in the profession that occur due to the birth of legislation in the health sector was not resolved properly and correctly. The use of health legal experts in health services in hospitals must reflect a sense of justice for all health workers based on Pancasila and the 1945 Constitution and special health law fields must be present in all hospitals and make health legal experts included in the health workforce group so that strength and Health legal authority is increasing so as to minimize the cases of malpractice that often occur lately. The use of health legal experts in health services in a hospital based on justice is the use of health legal experts in hospitals to prevent malpractice and create a balanced sense of justice between patients, the interests of health workers and the interests of hospitals.